2019
DOI: 10.3390/ijerph16224425
|View full text |Cite
|
Sign up to set email alerts
|

A Pill in the Lifeworld of Women in Burkina Faso: Can Misoprostol Reframe the Meaning of Abortion

Abstract: In Burkina Faso, induced abortion is socially stigmatized, condemned, disapproved and legally restricted to cases of rape, incest, fetal malformation or endangerment to the life of the mother. Many women often resort to unsafe procedures to induce abortion, which puts their health at great risk. Misoprostol, which is officially restricted to the treatment of postpartum hemorrhage or post-abortion care, is also used illegally by women to terminate their pregnancies. Misoprostol represents an addition to the exi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 36 publications
0
20
0
Order By: Relevance
“…For example, as a new generation of activists emerges whose mission is to make evidence-based information on misoprostol for self-induced abortion widely accessible, it will be important to track how they are faring and what are the social and political reverberations of their work in specific locales. For another example, drug traffickers, black market sellers, physicians, pharmacists, generic producers, and Internet pharmacies will continue to play significant roles in the circulation of misoprostol in many jurisdictions; such networks of distribution and profit making have only begun to be mapped and described (Drabo 2019; de Zordo 2016, 30). Finally, the impact of these many lives of misoprostol must continue to be followed into the hands and bodies of women themselves with attention to the varied and particular ways they are used and made meaningful.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, as a new generation of activists emerges whose mission is to make evidence-based information on misoprostol for self-induced abortion widely accessible, it will be important to track how they are faring and what are the social and political reverberations of their work in specific locales. For another example, drug traffickers, black market sellers, physicians, pharmacists, generic producers, and Internet pharmacies will continue to play significant roles in the circulation of misoprostol in many jurisdictions; such networks of distribution and profit making have only begun to be mapped and described (Drabo 2019; de Zordo 2016, 30). Finally, the impact of these many lives of misoprostol must continue to be followed into the hands and bodies of women themselves with attention to the varied and particular ways they are used and made meaningful.…”
Section: Resultsmentioning
confidence: 99%
“…In many jurisdictions where safe and/or legal abortion is unavailable or inaccessible, misoprostol now exists in a sort of gray market where the drug is legal and available for its original indication and may be used off-label in hospital by obstetricians (though not for medical abortion). Where the sale of misoprostol has been severely restricted or suspended by health authorities over concerns about “misuse”—in Brazil, Chile, and Mexico, for example—it can be acquired on the black market for highly inflated prices (de Zordo 2016; Drabo 2019). 4 Even in jurisdictions where abortion is legal and relatively accessible, the drug is still dogged by controversy.…”
Section: Misoprostol: a History Of Controversymentioning
confidence: 99%
“…The studies on uterine contractility have shown that a sustained level, rather than a high serum level, is required to develop regular uterine contractions [11]. Its uterotonic and cervical-ripening actions are widely used in obstetrics and gynecology; more than 30 dosage regimens are described regarding this matter [21,26] with side effects dose-related, usually transitory, and well-tolerated [27]. Manifestations of toxicity include hypertonic uterine contractions, fetal distress and death, hyperthermia, rhabdomyolysis, hypoxemia, respiratory alkalosis, and metabolic acidosis.…”
Section: Discussionmentioning
confidence: 99%
“…The plasma levels of misoprostol were sustained for a long time after vaginal administration (six hours vaginal route vs. four hours via sublingual route) [11,[18][19][20]. Adequate plasma levels enable vaginal misoprostol in specific applications such as second-trimester medical abortion [18,21].…”
Section: Introductionmentioning
confidence: 99%
“…Misoprostol’s uterotonic and cervical-ripening actions are generally used in obstetrics and gynecology. More than 30 dosage regimens are described regarding this matter [ 18 , 19 ], with side effects being dose-related, usually transitory, and well-tolerated [ 20 ]. Clinical manifestations of toxicity include hypertonic uterine contractions, fetal distress and death, hyperthermia, rhabdomyolysis, hypoxemia, respiratory alkalosis, and metabolic acidosis.…”
Section: Introductionmentioning
confidence: 99%